Elysium tide [large type] - Hannibal, James R. (Center Point Large Print, 2022)
"Dr. Peter Chesterfield is the top neurosurgeon at the Royal London Hospital. He's also a workaholic, and after a blow-up with a colleague, his boss orders him to attend a medical symposium at the luxurious Elysium Grand on the island of Maui. During a midnight walk on the beach, Peter pulls a woman with a skull fracture from the water. Despite all his skill, she dies in his arms, leaving him with only one clue to what happened to her: the word honu. Obsessed with finding the cause of his patient's death -- discovering what or who ripped the power over life and death from his surgeon's hands -- Peter becomes entangled in an ongoing investigation. He also becomes a source of deep irritation to detective Lisa Kealoha, who has jurisdiction over the case. The reluctant pair join forces, diving deep into Maui's evolving gang culture, and unearth a conspiracy that runs deeper than either could have imagined. Knowing too much is deadly -- and they must catch the killer before the killer catches them."--